Petrogenetic modelling of strongly residual metapelitic xenoliths within the southern Platreef, Bushveld Complex, South Africa - Johnson, Tim; Brown, M.; White, R. (Wiley - Blackwell, 2010)
Xenoliths of quartz-absent Fe-rich aluminous metapelite are common within the platinum group element-rich mafic/ultramafic magmatic rocks of the Platreef. Relative to well-characterized protoliths, the xenoliths are strongly depleted in K2O and H2O, and have lost a substantial amount of melt (>50 vol.%). Mineral equilibria calculations in the NCKFMASHTO system yield results that are consistent with observations in natural samples. Lower-grade rocks that lack staurolite constrain peak pressures to ~2.5 kbar in the southern Platreef. Smaller xenoliths and the margins of larger xenoliths comprise micro-diatexite rich in coarse acicular corundum and spinel, which record evidence for the metastable persistence of lower-grade hydrous phases and rapid melting consequent on a temperature overstep of several hundred degrees following their incorporation in the mafic/ultramafic magmas. In the cores of larger xenoliths, temperatures increased more slowly enabling progressive metamorphism by continuous prograde equilibration and the loss of H2O by subsolidus dehydration; the H2O migrated to xenolith margins where it may have promoted increased melting. According to variations in the original compositional layering, layers became aluminosilicate- and/or cordierite-rich, commonly with spinel but only rarely with corundum. The differing mineralogical and microstructural evolution of the xenoliths depends on heating rates (governed by their size and, therefore, proximity to the Platreef magmas) and the pre-intrusive metamorphic grade of the protoliths. The presence or absence of certain phases, particularly corundum, is strongly influenced by the degree of metastable retention of lower-grade hydrates in otherwise identical protolith bulk compositions. The preservation of fine-scale compositional layering that is inferred to be relict bedding in xenolith cores implies that melt loss by compaction was extremely efficient.